Increasing the Clinical Potential and Applications of Anti-HIV Antibodies - Hua, Casey K.; Ackerman, Margaret E. (Frontiers in Immunology, 2017)
Preclinical and early human clinical studies of broadly neutralizing antibodies (bNAbs) to prevent and treat HIV infection support the cinical utility and potential of bNAbs for prevention, post-exposure prophylaxis, and treatment of acute and chronic infection. Observed and potential limitations of bNAbs from these recent studies include the selection of resistant viral populations, immunogenicity resulting in the development of anti-drug (Ab) responses, and the potentially toxic elimination of reservoir cells in regeneration-limited tissues. Here, we review opportunities to improve the clinical utility of HIV Abs to address these challenges and further accomplish functional targets for anti-HIV Ab therapy at various stages of exposure/infection. Before exposure, bNAbs’ ability to serve as prophylaxis by neutralization may be improved by increasing serum half-life to necessitate less frequent administration, delivering genes for durable in vivo expression, and targeting bNAbs to sites of exposure. After exposure and/or in the setting of acute infection, bNAb use to prevent/reduce viral reservoir establishment and spread may be enhanced by increasing the potency with which autologous adaptive immune responses are stimulated, clearing acutely infected cells, and preventing cell-cell transmission of virus. In the setting of chronic infection, bNAbs may better mediate viral remission or “cure” in combination with anti-retroviral therapy and/or latency reversing agents, by targeting additional markers of tissue reservoirs or infected cell types, or by serving as targeting moieties in engineered cell therapy. While the clinical use of HIV Abs has never been closer, remaining studies to precisely define, model, and understand the complex roles and dynamics of HIV Abs and viral evolution in the context of the human immune system and anatomical compartmentalization will be critical to both optimize their clinical use in combination with existing agents and define further strategies with which to enhance their clinical safety and efficacy.